1994
DOI: 10.1021/bp00028a600
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ultrasonic Resonance Field Device for the Retention of Animal Cells

Abstract: This article describes two types of flow-through cell retention devices based on the concept of layered piezoelectric resonators. A single-chamber device is compared to a novel optimized steam-sterilizable prototype ultrasonic cell separator with improved acoustic design and an integrated cooling circuit, eliminating the problem of local temperature increase caused by the high amplitudes necessary to achieve the separation of animal cells with low acoustic contrast. This setup yields highly reproducible result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 13 publications
(4 reference statements)
4
60
0
Order By: Relevance
“…Doblhoff-Dier et al (1994) demonstrated that a higher input power was required to maintain a constant separation efficiency at high flow-rates. This trend is explained by the increased ultrasonic force required to retain the aggregated cells against the fluid drag, and by the lower mean fluid residence time.…”
Section: Ultrasonic Cell Retentionmentioning
confidence: 99%
“…Doblhoff-Dier et al (1994) demonstrated that a higher input power was required to maintain a constant separation efficiency at high flow-rates. This trend is explained by the increased ultrasonic force required to retain the aggregated cells against the fluid drag, and by the lower mean fluid residence time.…”
Section: Ultrasonic Cell Retentionmentioning
confidence: 99%
“…Planar USW systems may employ resonators that are larger than a wavelength and contain multiple pressure nodal planes [12,13], but for microfluidic scale devices, a resonant cavity with an axial dimension that is lower than the operating wavelength may be employed [14][15][16]. Such sub-wavelength resonators typically rely for their operation on precise positioning of the pressure node, to which particles will migrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the temperature difference between the recirculation flow and the resonator chamber is proven to be an important parameter for the stability of the acoustic field. In a previous study it is shown that an increase of the temperature difference, resulted in a decrease of the stability of the acoustic field and a decrease in the separation efficiency (Doblhoff-Dier et al, 1994;Gorenflo et al, 2002). Here the temperature in the conus of the acoustic separator increased from 34.2 to 34.9 due to the increase in the recirculation rate (Fig.…”
Section: Acoustic-separator Performancementioning
confidence: 75%